Social-Cultural Effects of Kahramanmaraş Earthquakes: The Case of Hatay - Suvari, Çakır Ceyhan; Karadağ, Barış; Elmacı, Nuran (Border Crossing, 2024)
Eleven cities in Turkey were affected by two major earthquakes centered in Kahramanmaraş on February 6, 2023. Official authorities announced that 15 million people were affected by the earthquakes. With these earthquakes, which are together called “the disaster of the century”, not only were people’s homes and workplaces destroyed, but their cultural spheres were also turned upside down. Family structures, habits, values, social memories, social relations, customs, and beliefs, that is, the cultures to which they owe their sociality, were also severely damaged. Unfortunately, as in most other development projects in our country, “culture”, which is the basic value that distinguishes humans from other living creatures, is not taken into account in disaster management projects. Any project that, is planned without considering the sophisticated needs, expectations, and habits of neither individuals nor society, cannot achieve the intended purpose, and even brings a greater financial burden on the country’s’ economy. In this research, the cultural damage caused by recent earthquakes in Hatay is attempted to be detected, and solutions for repairing such damage, and rebuilding social harmony are proposed. For this purpose, an anthropological fieldwork was conducted in Hatay’s’ Antakya, Defne and Samandağ districts between May 31 and June 4, 2023, and a series of interviews and conversations were held with the earthquake victims.